Effects of converting secondary forest on tropical peat soil to oil plantation on carbon storage - Ch'ng, Huck Ywih; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Jalloh, Mohamadu Boyie (Science Publications, 2009)
Problem statement: Peat has been identified as one of the major groups of soils found in Malaysia. Sarawak as the largest state in Malaysia has the biggest reserve of peat-land. There are about 1.5 million ha of peat-land in Sarawak, which are relatively under developed. As is the case with any plant, oil palm trees do sequester carbon as they g row. Nevertheless, the process of clearing forest i n order to establish a plantation may release carbon. Little studies have been done on the comparison of soil organic matter, soil organic carbon and yield of humic acids when secondary forest on peat soil i s converted to oil palm plantation. The objective of this study was to compare carbon s torage of secondary forest and early stages of oil palm plant ations on a tropical peat soil. Approach: Soil samples were collected from the secondary forest, 1 , 3, 4 and 5 year old oil palm plantations in Tatau district, Sarawak. Ten samples were taken at random with a peat auger at 0-25 and 25-50 cm depths. The bulk densities at these depths were determined by the coring method. The bulk density method was used to quantify the total carbon, total organi c matter, total nitrogen, humic acids and stable carbon at the stated sampling depths on per hectare basis. Results: There were no significant differences in the amounts of stable C of both seco ndary forest and different ages of the oil palm plantations at 0-25 and 25-50 cm soil depth. The am ounts of stable C in the secondary forest, 1, 3, 4 and 5 year old oil palm plantations at 0-25 cm dept h were generally higher than those in the 25-50 cm depth. This was attributed to higher yield of HA in the secondary forest, 1, 3, 4 and 5 year old oil p alm plantations soil partly due to better humification at the 0-25 cm soil depth. Conclusion: Conversion of secondary forest on peat to initial stages of oil p alm plantation seems to not exert any significant difference on carbon storage in tropical peat soil.